English Teacher's Experience in Implementing Gamification-Based Learning - Rama Dwika Herdiawan; Kiki Saputri; Nurhidayat, Eka (Papanda Publisher, 2023)
This study aims to reveal the English teacher's experience implementing gamification-based learning and the types of gamification applications or platforms teachers use in their teaching practice. This research uses a qualitative method with a narrative inquiry design. The participant of this research is a teacher who teaches English in one of the high schools in Majalengka. The results indicate that the English teacher is sufficiently experienced in implementing gamification, as they have utilized two types of gamification applications or platforms: Wordwall and Quizizz. The English teacher also expressed the benefits of gamification in the classroom, such as more effective learning outcomes that lead to increased student enthusiasm and motivation. Despite challenges such as limited resources and technical constraints, the English teacher has managed to overcome them, allowing gamified learning to thrive. This study also enables other researchers to explore new aspects related to gamified English language learning, and it is recommended that future studies involve more participants and extend over a longer period.